Political Parties' Right To Recall Against Legislative Members In The Perspective Of A Democratic Rule Of Law - Asriyani, Asriyani; Safrin, Mohamad; Muflih, Muhammad Naufal (Universitas Widya Gama Malang, 2024)
This article is entitled